The impact of the African Charter and the Maputo Protocol in selected African states - Victor Oluwasina Ayeni (Pretoria University Law Press (PULP), 2016)
About the publication The year 2016 was declared by the African Union as the African 'Year of Human Rights with Particular Focus on the Rights of Women' to commemorate and celebrate significant milestones in the realisation of human rights on the African continent. The year marks the 35th anniversary of the adoption of the African Charter on Human and Peoples' Rights (African Charter), 30th year since coming into force of the African Charter and 10 years since the inauguration of the African Court on Human and Peoples' Rights. Since its adoption, the African Charter has been supplemented by the Protocol on the Rights of Women in Africa (Maputo Protocol). All AU member states (with the exception of new comer South Sudan) are state parties to the African Charter, and 36 of them have accepted the Maputo Protocol. This book assesses the impact and effectiveness of the African Charter and the Maputo Protocol in 17 African countries, namely Burkina Faso, Cameroon, Côte d'Ivoire, Ethiopia, Gambia, Ghana, Kenya, Lesotho, Malawi, Mauritius, Nigeria, Sierra Leone, South Africa, Swaziland, Tanzania, Uganda and Zimbabwe. The book is the result of research conducted by selected alumni of the Centre for Human Rights' LLM in Human Rights and Democratisation in Africa programme. The Centre for Human Rights, which in 2016 is also celebrating 30 years of human rights education, intends to use this research as the basis for a continuously updated database on the impact of the African Charter and Maputo Protocol. Table of Contents Preface Introduction Victor Oluwasina Ayeni Burkina Faso Kounkinè Augustin Somé Cameroon Polycarp Ngufor Forkum Côte d'Ivoire Kounkinè Augustin Somé Armand Tanoh Ethiopia Meskerem Geset Techane The Gambia Satang Nabaneh Ghana Michael Gyan Nyarko Kenya Saoyo Tabitha Griffith Paul Ogendi Lesotho Sizakele Hlatshwayo Malawi Sarai Chisala-Tempelhoff Seun Solomon Bakare Mauritius Meskerem Geset Techane Roopanand Mahadew Nigeria Victor Oluwasina Ayeni Sierra Leone Augustine Sorie Marrah South Africa Ofentse Motlhasedi Linette du Toit Swaziland Dumsani Dlamini Sizakele Hlatshwayo Tanzania Grace Kamugisha Kazoba Charles Mmbando Uganda Agaba Daphine Kabagambe Zimbabwe Tarisai Mutangi Conclusion Victor Oluwasina Ayeni Bibliography Questionnaire used for the study